Conduct Of Tracer Studies for Quality Assurance Mechanisms: A Basis for Curriculum Enhancement - Carla Carmela P. Ramos; Nancy M. Flores (RES MILITARIS, 2022)
The Higher Education Institutions (HEIs) share the common goal of producing highly principled and globally competent individuals to meet the needs of the industry. Through this, HEIs are mandated by the Commission on Higher Education (CHED) to conduct tracer studies periodically to monitor the employability or success of their graduates which aims to ensure the quality assurance of an institution. This study focused on designing a framework on as to how graduate tracer studies can be useful in the curriculum enhancement of degree programs for quality assurance that may encourage other institutions to use the same. Systematic literature review was utilized as the main method of the study. The researchers reviewed and analyzed twenty (20) published related literatures and studies to answer the objective with factual and/or research-based pieces of evidence. The framework design sought to help not only the Pangasinan State University (PSU) but also other institutions in providing support in the process of accreditation, improving the performance, service and quality of education in the different degree programs. Thus, implementing the framework model can certainly help sustain the UN Development Goal No.8 on decent work and economic growth likewise usable in ensuring the quality of education.